2019
DOI: 10.1016/j.jobcr.2018.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal efficacy of herbs

Abstract: The aim of our study was to find the antifungal activities at MIC of selected fifteen plant leaves extracts prepared in three different solutions (methanol and ethanol) against the opportunistic pathogen Candida albicans isolated from oral cavity infections. It may also help the clinician to treat the patient not only for the particular lesion that is present, but also to treat the infection by Candida albicans so as to reduce its potential to malignant transformation. Material n methods: Leaves extract of sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 13 publications
0
34
1
2
Order By: Relevance
“…The antifungal activity was evaluated using all 12 different fractions extracts of methanol and hexane and their mixtures using plant extract of W. coagulans against A. niger and C. albicans by the disc method [ 52 ]. The active biomolecules were resolved into simple W. coagulans plant molecules that exhibited antifungal activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The antifungal activity was evaluated using all 12 different fractions extracts of methanol and hexane and their mixtures using plant extract of W. coagulans against A. niger and C. albicans by the disc method [ 52 ]. The active biomolecules were resolved into simple W. coagulans plant molecules that exhibited antifungal activity.…”
Section: Resultsmentioning
confidence: 99%
“…The active principal molecules were measure and made visible by the zone of inhibition produced by the fraction molecules against the specific strains (Figure 9a-h). The antifungal activity was evaluated using all 12 different fractions extracts of methanol and hexane and their mixtures using plant extract of W. coagulans against A. niger and C. albicans by the disc method [52]. The active biomolecules were resolved into simple W. coagulans plant molecules that exhibited antifungal activity.…”
Section: Antifungal Activity Of Prepared W Coagulans Against a Nigermentioning
confidence: 99%
“…A recent study by Samadi et al. (2019) reported that of fifteen herbs randomly selected, extracts of Lawsoniainermis , Withaniasomnifer , Curcuma longa , Cymbopogon citrates, and Zingiberofficinale showed potent inhibitory effects and had potential to control growth of C. albicans .…”
Section: Question 4: What Are the Recent Advances (Since 2015) Regardmentioning
confidence: 99%
“…FIC index is defined as the sum of the MIC of each drug in combination, divided by the MIC of the drug used alone. An FIC index 0.5 is considered synergism; FIC index 0.5–4 is indifferent; and FIC index > 4 is antagonism (Odds 2003) Several mechanisms of action can involve inhibition of (a) germination and biofilm formation, (b) cell metabolism, (c) cell wall integrity, and (d) cell membrane plasticity or induction of apoptosis (Samadi et al., 2019).…”
Section: Question 4: What Are the Recent Advances (Since 2015) Regardmentioning
confidence: 99%
See 1 more Smart Citation